Developing and validating a multi-dimensional scale for operationalizing industrial service offering. Issue 2 (6th March 2017) - Partanen, Jukka; Kohtamäki, Marko; Parida, Vinit; Wincent, Joakim
Abstract : Purpose: The purpose of this paper is to develop a new scale for measuring the scope (i.e. breadth and depth) of industrial service offering. Design/methodology/approach: The scale and its constructs are developed by combining the key insights from prior literature and practitioners gained through expert interviews; validating the constructs by 3 item-construct validation rounds with 9 academic experts; and by testing and further revising the scale, with a sample of 91 manufacturing firms. Findings: The distinct contribution of the study is the construction and validation of a new multi-dimensional scale for operationalizing the scope of industrial service offering. In addition, the identified service categories (i.e. pre-sales services, product support services, product life-cycle services, R&D services and operational services) extend the current literature on service typologies. Research limitations/implications: The data are somewhat biased toward small- and medium-sized industrial firms. Hence, the development of the measurement in the context of large industrial firms provides one fruitful avenue for further research. Practical implications: For managers of industrial firms, the identified service categories provide novel insight on how to develop, bundle and commercialize industrial services to their varying customer segments. Originality/value: This study develops a multi-dimensional, fine-grained, statistical and relationship-level scale for measuring the scope of industrial service business. Moreover, this study tests and further develops the scale with quantitative empirical data.